Deconstructing complexities in the adoption of new forms in news media: a systematic literature review - Dipannita Das; Ashwani Kumar Upadhyay (Cogent Arts & Humanities)
The diverse forms of journalism adopted in the newsroom have redefined the news media landscape. This systematic review paper reviews fifty journal articles (2000 and 2021), including some of the new forms of journalism: data and network journalism, automated and virtual reality journalism, and augmented reality journalism. This paper fills the research gap by offering insights into these new forms of journalism cumulatively, contrary to the existing literature that discusses single forms. The findings reveal a shift in mainstream news media from traditional reporting methods. The adoption of new forms is part of the survival strategy in this competitive media market.